2008
DOI: 10.1007/s10531-008-9496-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of understory plants in undisturbed and disturbed tropical lowland forests of Little Andaman Island, India

Abstract: Species richness and density of understory plants were investigated in eight 1 ha plots, distributed one each in undisturbed and disturbed tropical evergreen, semievergreen, deciduous and littoral forests of Little Andaman island, India, which falls under one of the eight hottest hotspots of Biodiversity in the world viz. the Indo-Burma. One hundred 1 m -2 quadrats were established in each 1 ha plot, in which all the understory plants (that include herbs, undershrubs, shrubs and herbaceous climbers) were enume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
(30 reference statements)
1
22
0
Order By: Relevance
“…A modified importance value index (IVI) for each species was calculated by summing its relative density and relative frequency in each plot, following Rasingam and Parthasarathy (2009). A modified family importance value (FIV) for each family was estimated as the sum of relative diversity and relative density of the individuals in that family.…”
Section: A Excelsamentioning
confidence: 99%
“…A modified importance value index (IVI) for each species was calculated by summing its relative density and relative frequency in each plot, following Rasingam and Parthasarathy (2009). A modified family importance value (FIV) for each family was estimated as the sum of relative diversity and relative density of the individuals in that family.…”
Section: A Excelsamentioning
confidence: 99%
“…Notably, Dipterocarpaceae is the dominant family in the three Asian sites, comprising about 14% of the 1-2 cm DBH trees in Asian forests and dominating the largest SAM class (Losos and Leigh, 2004;LaFrankie et al, 2006). Though available evidence shows that non-dipterocarp forests of Asia differ a lot from dipterocarp forests with respect to forest structure, species diversity and taxonomic composition of overstory trees (Cao and Zhang, 1997;Hamann et al, 1999;Kessler et al, 2005;Zheng et al, 2006), we still know little about the patterns of understory in the non-dipterocarp forests of tropical Asia except for some studies carried out in tropical evergreen forest of India (Rasingam and Parthasarathy, 2009). Consequently, our knowledge on the understory of tropical forests in Asia may be biased, more data from different areas are critically needed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, D'Amato et al (2009) indicated higher abundance, richness and diversity of understory species in old-growth forests compared to second-growth forests in hemlock forests in western Massachusetts. In contrast, some studies indicated a lower abundance of ground flora under undisturbed, abundant overstory in comparison to disturbed and more open overstories (Kumar and Ram, 2005;Nath et al, 2005;Rasingam and Parthasarathy, 2008). However, in these studies, ground species were taken as a whole when comparing disturbed with undisturbed forests and there are also certain factors that can influence the comparison, such as individual species characteristics and grazing pressure (Albrecht and McCarthy, 2009;Martin et al, 2009).…”
Section: Discussionmentioning
confidence: 97%